Gene expression changes during caste-specific neuronal development in the damp-wood termite Hodotermopsis sjostedti - Miyakawa Hitoshi; Ishikawa Asano; Okada Yasukazu; Ishikawa Yuki; Koshikawa Shigeyuki; Miura Toru (BMC Genomics, 2010)
Abstract Background One of the key characters of social insects is the division of labor, in which different tasks are allocated to various castes. In termites, one of the representative groups of social insects, morphological differences as well as behavioral differences can be recognized among castes. However, very little is known about the neuronal and molecular bases of caste differentiation and caste-specific behavior. In almost all termite species, soldiers play defensive roles in their colonies, and their morphology and behavior are largely different from workers (or pseudergates). Therefore, we predicted that some genes linked to defensive behavior and/or those required for neuronal changes are differentially expressed between workers and soldiers, or during the soldier differentiation, respectively. Results Using the brain and suboesophageal ganglion (SOG) of the damp-wood termite Hodotermopsis sjostedti, we first screened genes specifically expressed in soldiers or during soldier differentiation by the differential display method, followed by quantitative real-time polymerase chain reaction. No distinctive differences in expression patterns were detected between pseudergates and soldiers. In the course of soldier differentiation, however, five genes were found to be up-regulated in brain and/or SOG: 14-3-3epsilon, fibrillin2, beta-tubulin, ciboulot, and a hypothetical protein containing a SAP motif. Some of these genes are thought to be associated with cytoskeletal structure or motor-associated proteins in neuronal tissues. Conclusion The identified five genes could be involved in soldier-specific neuronal modifications, resulting in defensive behaviors in termite soldiers. The temporal expression patterns of these genes were consistent with the neuronal changes during soldier differentiation, suggesting that molecular machineries, in which the identified factors would participate, play important roles in behavioral differentiation of termite soldiers.